Implementasi Tri-N Berbasis Project Based Learning dalam Peningkatan Kompetensi Menulis Teks Prosedur Pembuatan Patung - Yazid Firdiawan; Sri Haryati Rahayuningsih; Siti Rochmiyati; Moh Rusnoto Susanto (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The low ability of sixth graders in writing procedural texts on sculpture making is attributed to a lack of understanding of procedural texts, difficulties in communicating knowledge into written form, and challenges in constructing effective sentences. This research aims to enhance the ability of sixth graders in writing procedural texts on sculpture making through the application of the Merdeka Belajar approach integrated with Project Based Learning (PjBL) and Tri-N. The study employed a Classroom Action Research (CAR) methodology, conducted in three cycles. Each cycle consisted of planning, implementation, observation, and reflection phases. The subjects of the study were sixth graders from SD Negeri Candiyasan Wonosobo. Data were collected through interviews, observations, and procedural text writing tests. The findings revealed a significant improvement in the ability of sixth graders to write procedural texts on sculpture making. In the first cycle, the pass rate for the procedural text writing test remained relatively low at 10%. In the second cycle, there was a significant increase in the pass rate for the procedural text writing test to 38%. The third cycle demonstrated optimal results, where almost all students achieved the pass rate, showing an increase of 52%. Therefore, it can be concluded that the Merdeka Belajar approach integrated with PjBL and Tri-N is effective in enhancing the ability of sixth graders to write procedural texts on sculpture making at SD Negeri Candiyasan Wonosobo.